Para a história da Schopenhauer-Gesellschaft no centenário da sua fundação - Fazio, Domenico (2011)
From the important work published in 2010 by teacher Fabio Ciraci In lotta per Schopenhauer. La “Schopenhauer-Gesellschaft” fra ricerca filosofica e manipolazione ideologica (1911-1948), the present article weaved considerations about the decisive period faced by the Schopenhauer-Gesellschaft, whose “fight” principal was realized in the sense of avoid the use of Schopenhauer thinking for an ideological end for part of Nazi and of fascism between the years 10 and 40 of past century.